Policy diffusion, domestic politics and social assistance in Lesotho, 1998-2012 - Maria Granvik (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Lesotho is a small Southern African country that has introduced two national cash transfer programmes, the Old Age Pension and the Child Grant Programme. Although Lesotho has followed what has been called the 'Southern African model', the introduction of the Old Age Pension was not the result of an explicit process of cross-national policy diffusion. The Child Grant Programme was initially driven by international organizations, but the dynamics were not Southern African, and the Lesotho Government quickly took ownership of the initiative. Unlike in many other parts of Africa, these reforms were not resisted by domestic political elites. The Old Age Pension was championed by the Prime Minister, with support from the Minister of Finance. The reforms were rooted in both socioeconomic changes, with the AIDS pandemic highlighting the inadequacy of extended familial responsibility for the poor, and political change, with the (possibly short-lived) restoration of stable democratic competition in the early 2000s opening the political space for programmatic reform.
Keywords: D63; H53; I38; N37; 330; Lesotho; policy diffusion; cash transfers; social pensions; HIV/AIDS; orphaned and vulnerable children